Multidisciplinary management of an intra-sellar cavernous hemangioma: Case report and review of the literature. (June 2018) - Chibbaro, S.; Cebula, H.; Ganau, M.; Gubian, A.; Todeschi, J.; Lhermitte, B.; Proust, F.; Noel, G.
Highlights: Sellar ECH should be considered in patients presenting with visual dysfunction. Gross total removal in this pathology carries high morbidity and mortality rates. Biopsy/partial resection with radiotherapy is the safest and most effective strategy. Abstract: Extra-axial cavernous hemangiomas (ECH) are rare vascular lesions with a tendency to grow within the medial structures of the middle cranial fossa. This pathological entity lacks specific symptoms, and falls into the category of differential diagnosis of space occupying lesions in the cavernous sinus (CS) with or without sellar involvement, including those of tumoral, vascular and inflammatory nature. Of note, ECH can also be indolent, and is at times discovered incidentally during autopsy investigations. On radiological studies, ECH with sellar extension are frequently mistaken at first for pituitary adenomas. Total removal of intrasellar-CS ECH is technically demanding and burdened by remarkable morbidity and mortality rates, mostly related to the complex neuroanatomy of the CS-sellar region (i.e., peri and postoperative bleeding, and transitory or permanent nerve palsies, hormonal deficits). Consequently, only a few cases of successful total removal have been reported so far in the literature. Surgical debulking with cranial nerve decompression followed by stereotactic radiosurgery is currently considered the best alternative to total removal when the latter carries excessive perioperative risks. We present a rare case of a mainly located intrasellar ECH extending to the left CS discussing its clinical features and focusing on the most relevant aspects of the surgical management along with a review of the pertinent literature.